Ragam dan Morfoteknologi Artefak di Situs-Situs Neolitik Sepanjang Ci Langla Bagian Hilir, Kabupaten Tasikmalaya - Nurul Laili; Anton Ferdianto (Kemendikbud, 2020)
Neolithic sites in the Karangnunggal Region along Ci Langla, starting from upstream to downstream. This paper will reveal the variety of neolithic artifacts in Ci Langla downstream. Thus it will be known about the activities of human life supporting neolithics in the area. Research on the distribution patterns and influencing factors is expected to be able to provide clues about human behavior patterns in utilizing space. The method used in the cultural approach focuses on archeological material or direct observation of artifacts (artifact oriented analysis). The artifacts analyzed are related to the activities of the adze workshop.